The Influence of Quantum Learning Models on Scientific Attitude - Nugraha, Widdy Sukma; Evianty, Evin Dwi (Universitas Sebelas Maret, 2021)
The problem of this research was the scientific attitude that was consist of five dimensions, such as curiosity attitude, respect on the data, perseverance, cooperation with others, and sensitive on the environment of fifth grade. The objective of this research was to know the influence of quantum learning model on the students’ scientific attitude of fifth grade in science subject. The method used quasi experimental with Nonequivalent Control Group design. The technique of collecting sample used saturation sampling. VA class as an experimental group that consist of 20 students. And VB class as control group that consist of 20 students. The instruments used questionnaire and observation. The technique of analysis in this research used t-test. It was aimed to find out the influence of quantum learning model on the students’ scientific attitude. The result of this research showed that quantum learning model was significant influential on the students’ scientific attitude of fifth grade in the material of panas dan perpindahannya. It took from the result of calculating data that showed sig. (2-tailed) 0.011 < 0.05. Thus, it showed that Ha was accepted. Therefore, it could be concluded that using quantum learning model can influence the students’ scientific attitude in science subject.